Contextual Morphological Interference in Indonesian Utterances by English Speakers on Social Media Contents - Nisa Halisa Hakim; Hayatul Cholsy (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Differences in morphological patterns between English and Indonesian often pose challenges for foreign learners in forming words accurately and may lead to morphological errors that cause misinterpretation in communication. This study aims to identify the forms and contextual patterns of morphological interference in Indonesian utterances produced by English speakers, as well as to investigate the underlying factors contributing to such interference. The research specifically focuses on social media content, a domain that remains underexplored in previous studies. A qualitative research approach with a descriptive analysis model was employed. The analysis was based on five main theoretical frameworks, namely theories of Indonesian word formation, English word formation, language interference, informal language use, and Indonesian language learning for foreign speakers (BIPA). The data, consisting of Indonesian utterances by English speakers, were collected from 15 videos from each of two YouTube channels published between 2020 and 2025 using observation and note-taking techniques. The analysis revealed 80 instances of contextual morphological interference, categorized into prefix omission (28 cases), suffix omission (20 cases), simulfix omission (21 cases), and errors in the reduplication process (11 cases). These data were analyzed to identify the forms and patterns of morphological interference, with support from a comprehensive literature review. The results indicate that interference is manifested not only through errors but also through the contextually appropriate use of morphological elements. The primary factors contributing to interference include the transfer of first-language (L1) patterns, limited knowledge of Indonesian morphological rules, and insufficient instructional emphasis on morphology within language learning. These deviations therefore, do not solely reflect a lack of linguistic competence but also indicate learners' developing sensitivity to Indonesian morphological structures. This study makes a significant contribution to error analysis research and offers pedagogical insights for enhancing morphology instruction within BIPA (Bahasa Indonesia bagi Penutur Asing) program.